Early penile-only metastasis of urothelial bladder carcinoma - Georges Abi Tayeh; Albert Semaan; Julien Sarkis; Josselin Abi Chebel; Chadi Waked (Future Science OA, 2020)
Penile metastasis rarely occurs as a unique and early distant recurrence of urothelial bladder carcinoma. A 77-year-old male underwent a radical cystoprostatecomy for a pT3a urothelial bladder cancer. Preoperative imaging workup concluded to a disease confined to the bladder. The patient consulted 5 months later for a penile induration. Computed tomography imaging revealed a suspicious penile nodule with no other nodal or visceral lesion. Total penectomy after a confirmatory biopsy confirmed the infiltration of the corpora cavernosa, the corpus spongiosum and the urethra by a urothelial metastasis of bladder cancer. Distant recurrences after radical surgery for locally advanced bladder cancer may occur as a unique early metastasis located to the penis.